Heaving wave energy converter-type attachments to a pontoon-type very large floating structure. (15th September 2020) - Nguyen, H.P.; Wang, C.M.
Highlights: A conceptual design of VLFS with heaving WEC-type attachments is studied numerically. In head seas, the power capture factor is up to 0.22 for short waves, 0.65 for long waves. Proposed attachments outperform the previously proposed methods in extracting energy from long or large oblique waves. Power produced may increase significantly by using flexible connections between VLFS modules. Abstract: This study proposes heaving wave energy converter (WEC) - type attachments to a pontoon-type very large floating structure (VLFS) for extracting wave energy and reducing the hydroelastic response of the VLFS. Each heaving WEC-type attachment consists of a linear Power Take-Off (PTO) system connected to VLFS at one end and to the seabed at the other end. The performance of heaving WEC-type attachments is investigated with respect to PTO damping coefficient and stiffness, locations and the number of PTO systems, VLFS flexural rigidity, VLFS module connection design, wave period and incident wave angle. For the fluid–structure interaction analysis, the Mindlin plate theory is adopted for modelling VLFS, while the linear wave theory is adopted for modelling fluid motions. The hybrid finite element – higher order boundary element method (FE-HOBEM) is employed to solve the fluid–structure interaction problem. It is found that, for long waves and large oblique waves, the present WEC-VLFS system outperforms the previously proposed WEC-VLFS systems in terms of the power produced.